Use of Water Quality Index (WQI) for Assessment of Groundwater Quality - Anuj Goyal (International Journal of Advanced Science and Technology, 2020)
Various anthropogenic activities are adversely affecting the quality of groundwater particularly shallow groundwater. Hence monitoring of groundwater has become indispensable to maintain the quality at a certain safe limit. In the current study, Water quality index (WQI) has been considered for assessing the quality of groundwater in nearby region of Varun Beverages, Mathura. In order to calculate WQI eight significant parameters namely pH, total hardness, alkalinity, chloride, total dissolved solids, electrical conductivity, nitrate and fluoride were used because these eight parameters contribute maximum for determining the drinking water quality. The WQI for the 20 samples have been determined & the computed. Analysis of WQI shows that 90% of water sample falls in the ‘Very Bad to Bad’ water category & only 10% lies in Medium category. It is observed that that none of the sample lies in "excellent to good" category indicating that the water is not fit for direct utilization and require proper treatment. After treatment, the water can be utilized for drinking purpose.